De amigo a enemigo interno: lo indígena en el discurso presidencial entre 2021 y 2022 (Monográfico) - Guaña Córdova, Cinthya Gabriela (2023)
The study records the results of the critical analysis of Guillermo Lasso’s political discourse from May to December 2021, and during June 2022, in the context of the protests that lasted 18 days. After almost 21 hours of material viewed and through a comparison between both time periods, the research finds that the population group that is mentioned as an ally of the government in the first period, becomes an internal enemy of the government during the second period. On the one hand, this quantitative-qualitative research collects data on the duration of the speeches, places of broadcast, themes and recurring actors and their respective times of approach. On the other hand, the comparison between timelines and the finding of similarities and differences between discourses make it possible to find the total change in the conception that the government had/has about the indigenous population in Ecuador. This work puts into practice the approaches of Gunther Dietz and Laura Mateos on the inclusion of multicultural discourse in political discourse as a form of alliance with historically excluded populations, which does not rule out the possibility of excluding them again from the same discourse.